Evaluasi Agronomis Pertumbuhan dan Ketahanan Hidup Bibit Semangka (Citrullus lanatus) pada Vertisol dengan Aplikasi Berbagai Pupuk Kandang - Marvin Jecson Pandu; Marlin Marhaeni Pe; Melinda. R.S. Moata; Hidayah Usman (Politeknik Negeri Lampung., 2026)
This study aimed to evaluate the effects of different types of organic manure on the growth and survival of watermelon (Citrullus lanatus) seedlings cultivated in Vertisol media. The treatments consisted of cattle, goat, and chicken manure, along with a non-fertilized control. Vegetative growth parameters observed included plant height, leaf number, and leaf area, while seedling survival was analyzed using the Kaplan–Meier method and log-rank test. The results showed that manure type significantly affected all vegetative growth parameters. Cattle manure produced the highest vegetative growth performance, followed by the control and goat manure treatments, whereas chicken manure resulted in the lowest growth response. The highest survival rate was observed in the cattle manure treatment (100%), followed by the control (93.75%) and goat manure (87.50%), while chicken manure showed the lowest survival rate (18.75%). Kaplan–Meier curves revealed that the chicken manure treatment experienced the most rapid decline in survival probability from the early observation period. The log-rank test demonstrated that differences among survival curves were statistically significant (log-rank χ² = 41.98; df = 3; p < 0.001), indicating that organic manure type significantly influenced seedling survival during the early nursery stage. Overall, the findings demonstrate that under Vertisol conditions, cattle manure provided the best combination of vegetative growth and survival stability of watermelon seedlings compared with the other treatments.